Functional Recovery Following Pertrochanteric Hip Fractures Fixated with the Dynamic Hip Screw vs. the Percutaneous Compression Plate. (2005) - Laufer, Yocheved; Lahav, Miriam; Lenger, Reuben; Sprecher, Elliot
Abstract : The Dynamic Hip Screw (DHS) is currently the most frequently used implant for the treatment of pertrochanteric hip fractures. The Percutaneous Compression Plate (PCCP) is a recently developed, alternative device that involves minimal invasive surgery. The objective of the present study was to compare functional recovery following these two surgical procedures. A total of 76 consecutive elderly subjects (mean age and standard deviation, 80.6 ± 5.5) following pertrochanteric hip fracture fixation were evaluated prospectively. Functional recovery was assessed 3 and 12 weeks and 2 years following surgery. Differences between groups 3 weeks postsurgery were found only in pain level during ambulation and in the weight-bearing capability of the operated extremity, which were both in favor of the PCCP. By 3 months, both groups had improved in all measures, but did not reach their preinjury level of independence. However, the PCCP group ambulated with fewer assistive devices and demonstrated better recovery of basic activities of daily living (BADL). While the majority of the subjects from both groups ambulated independently 2 years postsurgery, the PCCP group exhibited less pain during ambulation, was more independent in ADL, and required fewer assistive devices for ambulation. To summarize, the PCCP presents enhanced short- and long-term recovery of functional abilities in comparison to DHS. However, given the limited number of patients, further studies are necessary to substantiate these results.